Piezo‐Activated Atomic‐Thin Molybdenum Disulfide/MXene Nanoenzyme for Integrated and Efficient Tumor Therapy via Ultrasound‐Triggered Schottky Electric Field. Issue 9 (16th December 2022) - Wu, Yizhang; Song, Xueru; Zhou, Xiaoyu; Song, Renjie; Tang, Wenchao; Yang, Dingyi; Wang, Yong; Lv, Zhongyang; Zhong, Wei; Cai, Hong‐Ling; Zhang, Aimei; Wei, Jia; et al.
Abstract: Monolayer molybdenum disulfide (MoS2 ) nanoenzymes exhibit a piezoelectric polarization, which generates reactive oxygen species to inactivate tumors under ultrasonic strain. However, its therapeutic efficiency is far away from satisfactory, due to stackable MoS2, quenching of piezo‐generated charges, and monotherapy. Herein, chitosan‐exfoliated monolayer MoS2 (Ch‐MS) is composited with atomic‐thin MXene, Ti3 C2 (TC), to self‐assemble a multimodal nanoplatform, Ti3 C2 ‐Chitosan‐MoS2 (TC@Ch‐MS), for tumor inactivation. TC@Ch‐MS not only inherits piezoelectricity from monolayer MoS2, but also maintains remarkable stability. Intrinsic metallic MXene combines with MoS2 to construct an interfacial Schottky heterojunction, facilitating the separation of electron–hole pairs and endowing TC@Ch‐MS increase‐sensitivity magnetic resonance imaging responding. Schottky interface also leads to peroxidase mimetics with excellent catalytic performance toward H2 O2 in the tumor microenvironment under mechanical vibration. TC@Ch‐MS possesses the superior photothermal conversion efficiency than pristine TC under near‐infrared ray illumination, attributed to its enhanced interlaminar conductivity. Meanwhile, TC@Ch‐MS realizes optimized efficiency on tumor apoptosis with immunotherapy. Therefore, TC@Ch‐MS achieves an integrated diagnosis and multimodal treatment nanoplatform, whereas the toxicity to normal tissue cells is negligible. This work may shed fresh light on optimizing the piezoelectric materials in biological applications, and also give prominence to the significance of intrinsic metallicity in MXene. Abstract : Piezo‐activated Schottky nanoplatform TC@Ch‐MS is developed by self‐assembling between Ti3 C2 and chitosan‐exfoliated monolayer MoS2 . TC@Ch‐MS harvests superior reactive oxygen species under ultrasonic excitation, owing to the built‐in Schottky electric field; TC@Ch‐MS has superior photo‐thermal conversion efficiency and PTT performance, owing to the conductive layer constructed by interlayered MoS2 ; TC@Ch‐MS realizes the immunotherapy upon the synergy of NIR and ultrasound.